2021
DOI: 10.3389/fmicb.2021.642789
|View full text |Cite
|
Sign up to set email alerts
|

Metataxonomic Profiling of Native and Starter Microbiota During Ripening of Gouda Cheese Made With Listeria monocytogenes-Contaminated Unpasteurized Milk

Abstract: Unpasteurized milk is used to produce aged artisanal cheeses, which presents a safety concern due to possible contamination with foodborne pathogens, especially Listeria monocytogenes. The objective of this study was to examine the composition of the bacterial community in unpasteurized milk used to prepare Gouda cheese artificially contaminated with L. monocytogenes (~1 log CFU/ml) and assess the community dynamics and their potential interaction with L. monocytogenes during a 90-day ripening period using tar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…Through the changes in their own metabolism and the subsequent release of antimicrobial molecules, the lactic acid bacteria impact the growth of pathogens [ 70 ]. The dynamics of variation of the resident microbiota in control and L. innocua -inoculated cheese observed in our study are consistent with the findings of other research involving raw milk in the production of Gouda cheese [ 71 ]. The authors claimed that in the first phase of cheese production, the microbial populations were dominated by the starter microorganisms, whose main technological action was carried out with the lowering of the milk pH; during the maturation phase, the counts of these bacteria slightly decreased, and the bacteria were involved in other important enzymatic reactions such as lipolysis, proteolysis, and production of flavor compounds.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Through the changes in their own metabolism and the subsequent release of antimicrobial molecules, the lactic acid bacteria impact the growth of pathogens [ 70 ]. The dynamics of variation of the resident microbiota in control and L. innocua -inoculated cheese observed in our study are consistent with the findings of other research involving raw milk in the production of Gouda cheese [ 71 ]. The authors claimed that in the first phase of cheese production, the microbial populations were dominated by the starter microorganisms, whose main technological action was carried out with the lowering of the milk pH; during the maturation phase, the counts of these bacteria slightly decreased, and the bacteria were involved in other important enzymatic reactions such as lipolysis, proteolysis, and production of flavor compounds.…”
Section: Discussionsupporting
confidence: 92%
“…The authors claimed that in the first phase of cheese production, the microbial populations were dominated by the starter microorganisms, whose main technological action was carried out with the lowering of the milk pH; during the maturation phase, the counts of these bacteria slightly decreased, and the bacteria were involved in other important enzymatic reactions such as lipolysis, proteolysis, and production of flavor compounds. Furthermore, the authors stated that the inoculum of Listeria monocytogenes had no inhibitory effect on the relative abundance of starter populations, nor vice versa [ 71 ].…”
Section: Discussionmentioning
confidence: 99%
“…While the majority of cheeses are produced from cow’s milk, cheese from sheep, goats, buffalo, camels, and even donkeys is manufactured [ 43 ]. Genera common to all raw milk include Lactococcus , Lactobacillus , Leuconostoc , Streptococcus , and Enterococcus , although certain varieties are more strongly associated with one type or another, which impacts the microbiome of a final product [ 44 , 45 , 46 ]. For example, while the predominant genera in cow’s milk include Pseudomonas , Bacillus , Lactococcus , and Acinetobacter , the genera most common to raw camel’s milk include Enterococcus , Lactococcus , and Pediococcus [ 47 , 48 ].…”
Section: Fermented Foodmentioning
confidence: 99%
“…The quality of the cheeses also showed the differences between the treatments, which were probably due to the addition of the different starter cultures. According to Salazar et al [ 26 ], the addition of a known starter culture to unpasteurized milk makes it dominant in the developing product. In addition, Vázquez-Velázquez et al [ 27 ] found that the use of a starter culture helped keep the total pathogenic microbes in pasteurized cheese below standard maximum values.…”
Section: Resultsmentioning
confidence: 99%